Quality of life and relative importance: a comparison of time trade-off and conjoint analysis methods in patients with age-related macular degeneration. Issue 6 (17th January 2007) - Aspinall, P A; Hill, A R; Dhillon, B; Armbrecht, A M; Nelson, P; Lumsden, C; Farini-Hudson, E; Brice, R; Vickers, A; Buchholz, P
Abstract : Aim: To investigate the relative priorities in quality of life (QoL) in patients with age-related macular degeneration (AMD). Methods: Measures of visual function, QoL and utility associated with visual loss were obtained from 122 patients with AMD classified according to macular morphology. The two methods of utility assessment were time trade-off (TTO) and conjoint analysis (CA), which have been recommended by the UK's National Institute of Clinical Excellence as techniques for the assessment of healthcare priorities. Results: Results show that the two methods for assessing utility are poorly related: TTO relates moderately to visual function and disease severity but CA does not. CA identified two different subgroups of patients: one with outdoor mobility and the other with reading as their main priority. Conclusion: Further work is needed and caution required in interpreting data obtained using these methodologies for determining their relative importance in vision-related QoL studies.